2014
DOI: 10.1111/ggi.12367
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in elderly patients with asthma: Association with control of the disease and concomitant treatment

Abstract: Aim:The incidence of concomitant conditions increases with age. In elderly patients, the presence of comorbidities has been related to the course and severity of asthma. The aim of the present study was to assess the impact of comorbidities and concomitant treatment on asthma control and severity in older adults.Methods: A total of 93 elderly (age >65 years) and 78 younger (age 30-50 years) asthmatic patients were randomly selected from a database including 1755 asthmatics. Evaluation consisted of a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…There was no correlation between the presence of comorbid conditions and asthma control, severity or frequency of exacerbations in older patients [76]. To our knowledge, there are no studies demonstrating clear differences between efficacy of AIT between elderly and younger adults.…”
Section: Role Of Allergen Immunotherapy In the Elderly Patientmentioning
confidence: 70%
“…There was no correlation between the presence of comorbid conditions and asthma control, severity or frequency of exacerbations in older patients [76]. To our knowledge, there are no studies demonstrating clear differences between efficacy of AIT between elderly and younger adults.…”
Section: Role Of Allergen Immunotherapy In the Elderly Patientmentioning
confidence: 70%
“…[2729] Other studies have also reported significantly higher prevalence of comorbidities in elderly in comparison with nonelderly COPD patients. [30,31] Indeed, up to 90% COPD patients can have at least one comorbidity. [32,33] …”
Section: Discussionmentioning
confidence: 99%
“…otros estudios han encontrado sólo una significación límite entre el asma y la HTa 26 . en cuanto a la asociación entre el número de comorbilidades y el grado de control del asma, los escasos estudios que lo han comunicado no han encontrado asociación 43 , al igual que el nuestro.…”
Section: Resultsunclassified